Investigating Learners’ Understanding on Politeness and Gender of Advertisements in Teaching Sociolinguistics - Fathira, Vina; Utami, Silvia (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2018)
This research was based on the researchers’ curiosity to investigate learners’ understanding politeness and gender concept of advertisements. The advertisements were watched frequently by the learners of this digital era, nowadays. Then, the politeness and gender concept sometimes can be seen in the advertisement. Politeness and gender is part of sociolinguistics subject for English literature. The aim of the research was to investigate learners’ understanding in identifying politeness and gender concept existed in advertisement. The method used in this research was quantitative followed by qualitative as additional information. The population and sample of this research was the sixth semester learners of STIBA Persada Bunda. There were 10 learners as population as well as sample of this research. The data collection technique was gained by asking the learners to choose the multiple choices of politeness and gender questions by watching the video of advertisement. Then, after collecting the data, the researchers evaluated and analyzed the test of each learner. The result of this research showed that the learners’ understanding in identifying politeness and gender existed in advertisements is in low level with score 51,5 “poor” category. The factors that affected the learners’ understanding were the lack of learners’ understanding of theoretical concept of politeness and gender, and hard for learners to differentiate gender concept of sex concept.